ANALYSE DE LA VARIABILITÉ TEMPORELLE ET SPATIALE DES SÉRIES CLIMATIQUES DU NORD DU TOGO ENTRE 1960 ET 2010 - Badjana Hèou Maléki; Hounkpè koffi; Wala Kpérkouma; Batawila Komlan; Akpagana Koffi; Edjamé Kodjovi Sidéra (European Scientific Journal, ESJ, 2014)
Understanding the spatial and temporal climate variability at reducedscales is fundamental for answering many questions that arise about theimpacts of climate change, local vulnerability and development projects.This study consisted to analyze the spatial and temporal variability of rainfalland temperature time series in the North of Togo between 1960 and 2010,using Hanning low-pass filter of first order, rainfall indexes, statistical testsof stationarity of climate time series and Kriging. The results show thatclimate variability has resulted particularly in strong interannual fluctuationsin rainfall and a succession of dry and wet periods on the one hand andperiods of high and low temperature on the other hand. Unlike temperaturethat has increased at all stations, the temporal at-site analysis shows thatrainfall is stationary at the stations of Dapaong, Niamtougou and Kara whileit has a decreasing trend at the stations of Borgou, Mango and Sokodé.Several break points were also detected and causes deserve a particularanalysis. Though the results of this study constitute important and necessaryindicators for climate risks assessments, the improvement and strengtheningof monitoring systems become important to better characterize and predict local climate changes in order to reduce the vulnerability of localpopulations.